In vitro efficacy of tavaborole topical solution, 5% after penetration through nail polish on ex vivo human fingernails. (18th August 2018) - Gupta, Aditya K.; Vlahovic, Tracey C.; Foley, Kelly A.; Lowe, Nicole Gellings; Turner, Rob; Brown, Marc; Hall, Steve
Abstract: Background: Topical antifungal treatments for onychomycosis are applied to clean, unpolished nails for 48 weeks or longer. Patients often wish to mask their infection with nail polish yet there is no evidence to suggest antifungal efficacy in the presence of nail polish. Objective: To determine if tavaborole retains the ability to penetrate the nail plate and inhibit fungal growth in the presence of nail polish. Method: Tavaborole was applied to human fingernails painted with 2 or 4 coats of nail polish, and unpainted nails in an ex vivo model. Nails were mounted on TurChub ® chambers seeded with Trichophyton rubrum and allowed to incubate for 7 days. Antifungal activity was assessed by measuring zones of inhibition. Results and conclusion: Tavaborole exhibited antifungal activity in all experimental groups. The zones of inhibition of T. rubrum for all experimental groups (2 or 4 coats of polish, unpolished) were greater than infected controls (polished and unpolished), p s < .001. Tavaborole penetrates polished nails and kills T. rubrum in this ex vivo model.